(untitled) (Research, Society and Development, 2022)
Rainfall probability studies are important for the adequate design of public works, such as drainage systems, and for soil management and conservation practices that should be implemented by farmers. The objective of this study was to study the probability of rainfall episodes using monthly and annual precipitation data for the municipality of Bom Jesus. We worked with the period from 1960 to 2018, which were analyzed for consistency, homogenization and filling of gaps and ordering. Daily, monthly, and annual precipitation information was obtained, generating information about daily and monthly absolute maximum values; monthly and annual maximum, average, and minimum values. The monthly precipitation was fitted to the gamma distribution. The probability of rainfall occurrence in the municipality of Inconfidentes is variable for each month, but follows a pattern over the years. Although months like January, February and October, are more critical with a probability of 4.4%, 2.2% and 6.7%, respectively for the occurrence of rainfall of more than 90 mm daily and a lower incidence in the months of June and July with a probability of approximately 0%. The possibility of precipitation anomalies is real even with the low probability. Determining the availability of water, the probability of occurrence of extreme events and the return period can make an optimized planning, helping in the development of various types of projects, bringing benefits to the local society.